Characteristic temperatures and microhardness of (ZnO)x-(AlF3)y-(TeO2)z tellurite glass systems - Sidek, H. A. A.; El-Mallawany, R.; Rosmawati, S.; Yahya, A. K. (National Institute of Materials Physics, National Institute of Optoelectronics, 2016)
Glass transition temperature Tg and softening temperature Ts were measured by the differential thermogravimetric analysis DTA in the temperature range 300-850 K of ternary zinc oxyfluoro tellurite (ZOFT) with the composition (ZnO)x-(AlF3)y-(TeO2)z where (5 D, softening temperatures Ts(calc) and microhardness Hvof ternary zinc oxyfluoro tellurite (ZOFT) have been calculated by using ultrasonic velocities data. The compositional dependence of these physical quantities were discussed to understand the rigidity and compactness of the glass system studied.